The underground railroad - Whitehead, Colson 1969-; Britell, Nicholas 1980- (The Criterion collection, 2024)
"A monumental reimagining of American history, Barry Jenkins’s adaptation of Colson Whitehead’s Pulitzer Prize–winning 2016 novel is a harrowing and rhapsodic journey through a still-echoing past. Weaving together historical fiction with moments of magical realism, The Underground Railroad is a full sensory immersion into the world of Cora (Thuso Mbedu), who, fleeing slavery, embarks on a treacherous quest for freedom—and is menaced by violence, supported by a clandestine community fighting for liberation, and haunted by the people she loses along the way. With images of searing power and stirring poetry, Jenkins delivers an epic saga of survival and resilience that pushes the limited-series format to new heights of cinematic transcendence." [criterion.com]
Original: USA, Großbritannien, Indien, Thailand 2021
Director-approved four-DVD special edition features: 4K digital master, approved by cowriter-director Barry Jenkins ; new audio commentary featuring Jenkins and, on select chapters, cinematographer James Laxton and lead editor Joi McMillon, with an introduction by the director ; new graphic-novel adaptation of "Genesis," an unfilmed chapter of The Underground Railroad written by Jenkins and Nathan C. Parker, drawn by Valentine De Landro, with an introduction by Jenkins ; The Gaze, a companion film by Jenkins, with a new introduction by the director ; deleted scenes, with a statement by Jenkins ; seven teasers made by Jenkins, with a new introduction by the director ; building "The Underground Railroad," a short program featuring Jenkins and production designer Mark Friedberg discussing the creation of the train-station sets ; English subtitles for the deaf and hard of hearing and English descriptive audio ; plus: An essay by critic Angelica Jade Bastién
Bildformat 1.78:1, 2.39:1
Keywords: Film; DVD-Video